Coexistence of Photosynthetic Marine Microorganisms, Viruses and Grazers: Towards Integration in Ocean Ecosystem Models - Paul Frémont; Stephen J. Beckett; David Demory; Eric Carr; Christopher L. Follett; Debbie Lindell; David Talmy; Stephanie Dutkiewicz; Joshua S. Weitz (Environmental Microbiology, 2026)
Photosynthetic microorganisms are responsible for primary production at the base of the marine food web and influence global biogeochemistry. Their growth is balanced by mortality processes, including zooplankton grazing and viral lysis. These predators coexist despite competing for the same microorganisms. Here, we develop a community model of photosynthetic microorganisms, grazers and viruses that incorporates elemental quotas and is suitable for ocean ecosystem models. We evaluate the extent to which coexistence is facilitated by: (i) explicit infected phytoplankton; (ii) heterogeneity in susceptibility to viral infection; and (iii) higher‐order mortality for the predators. We show a trade‐off between the virus latent period and virulence in facilitating coexistence. The latent period generates oscillations that reduce the growth rate of the free virus, promoting coexistence. Heterogeneity in susceptibility supports coexistence through resource partitioning, while higher‐order mortality widens the coexistence regime. The model outcomes are sensitive to viral life history traits, including the percentage of infected cells and the balance between virally‐ and zooplankton‐induced mortality. Leveraging algebraic model equilibria, we identify parameter combinations that yield realistic ecological properties in simplified epipelagic environments. Our models suggest that efforts to embed virus dynamics in ocean ecosystem models should include moderate to strong resistance to viral infection.

Viruses in multi-scale ocean models: challenges and opportunities - David Talmy; Cristina Howard-Varona; Damien Eveillard; Markus Covert; Matthew B. Sullivan (Frontiers in Marine Science, 2025)
While viruses affect the flow of elements and energy at a planet-wide scale through lysis, gene transfer, and metabolic reprogramming, they are yet to be included in planetary-scale models of ecosystem function and nutrient cycling. Here, we review recent advances incorporating viruses into ocean models and ask: what barriers remain? To address these challenges, we argue for a new generation of ocean models that are fully representative of the multifaceted influences of viruses across scales of organization. We describe ways to achieve this by integration of existing models built across scales, from molecules to ecosystems and the Earth System. To accelerate these advances, we emphasize the need for systematic, intercalibrated datasets for diverse experimental virus-host systems, wider application of new technologies to monitor in situ viral infections, and new software to integrate models across scales. Resolution of viruses within multi-scale models will open the door to assessing current biological uncertainties related to the impact of viral infection on nutrient retention in the surface ocean, carbon sequestration to depth, and the sensitivity of these processes to climate change.

Linear scaling between microbial predator and prey densities in the global ocean - Harshana Rajakaruna; Anne Willem Omta; Eric Carr; David Talmy (Environmental Microbiology, 2023)
It has been proposed that microbial predator and prey densities are related through sublinear power laws. We revisited previously published biomass and abundance data and fitted Power‐law Biomass Scaling Relationships (PBSRs) between marine microzooplankton predators ( Z ) and phytoplankton prey ( P ), and marine viral predators ( V ) and bacterial prey ( B ). We analysed them assuming an error structure given by Type II regression models which, in contrast to the conventional Type I regression model, accounts for errors in both the independent and the dependent variables. We found that the data support linear relationships, in contrast to the sublinear relationships reported by previous authors. The scaling exponent yields an expected value of 1 with some spread in different datasets that was well‐described with a Gaussian distribution. Our results suggest that the ratios Z / P , and V / B are on average invariant, in contrast to the hypothesis that they systematically decrease with increasing P and B, respectively, as previously thought.

Trophic model closure influences ecosystem response to enrichment - Anne Willem Omta; Elizabeth A. Heiny; Harshana Rajakaruna; David Talmy; Michael J. Follows (Ecological Modelling, 2023)

A model of algal‐virus population dynamics reveals underlying controls on material transfer - Audra Hinson; Spiro Papoulis; Lucas Fiet; Margaret Knight; Priscilla Cho; Brielle Szeltner; Ioannis Sgouralis; David Talmy (Limnology and Oceanography, 2023)
The influence of viruses on nutrient cycles and energy transfer in aquatic systems is important, yet still being determined. We developed a dynamic model to capture the population dynamics of algal hosts and their viruses. The model was fitted to literature data of population dynamics during laboratory one‐step infection experiments. Model parameters that underlie population dynamics were quantified in diverse algal groups, covering 7 different algal classes, 14 different host genera, and 32 different virus genotypes. The hypothesis that trade‐offs exist between traits that underlie population dynamics was evaluated. We report a possible virus size‐dependent trade‐off between the rate at which viruses can initiate infection, and the efficiency of carbon transfer from hosts to viruses upon lysis. We hypothesize that slower rates of infection in large viruses, due to slower rates of molecular diffusion, are compensated by enhanced utilization of host resources. Our approach provides a quantitative trait‐framework for understanding and quantifying virus activity in diverse natural communities.

Marine phytoplankton resilience may moderate oligotrophic ecosystem responses and biogeochemical feedbacks to climate change - Adam C. Martiny; George I. Hagstrom; Tim DeVries; Robert T. Letscher; Gregory L. Britten; Catherine A. Garcia; Eric Galbraith; David Karl; Simon A. Levin; Michael W. Lomas; Allison R. Moreno; David Talmy; et al. (Limnology and Oceanography, 2022)
Are the oceans turning into deserts? Rising temperature, increasing surface stratification, and decreasing vertical inputs of nutrients are expected to cause an expansion of warm, nutrient deplete ecosystems. Such an expansion is predicted to negatively affect a trio of key ocean biogeochemical features: phytoplankton biomass, primary productivity, and carbon export. However, phytoplankton communities are complex adaptive systems with immense diversity that could render them at least partially resilient to global changes. This can be illustrated by the biology of the Prochlorococcus “collective.” Adaptations to counter stress, use of alternative nutrient sources, and frugal resource allocation can allow Prochlorococcus to buffer climate‐driven changes in nutrient availability. In contrast, cell physiology is more sensitive to temperature changes. Here, we argue that biogeochemical models need to consider the adaptive potential of diverse phytoplankton communities. However, a full understanding of phytoplankton resilience to future ocean changes is hampered by a lack of global biogeographic observations to test theories. We propose that the resilience may in fact be greater in oligotrophic waters than currently considered with implications for future predictions of phytoplankton biomass, primary productivity, and carbon export.

An empirical model of carbon flow through marine viruses and microzooplankton grazers - David Talmy; Stephen J. Beckett; Darcy A. A. Taniguchi; Corina P. D. Brussaard; Joshua S. Weitz; Michael J. Follows (Environmental Microbiology, 2019)
Summary Viruses and microzooplankton grazers represent major sources of mortality for marine phytoplankton and bacteria, redirecting the flow of organic material throughout the world's oceans. Here, we investigate the use of nonlinear population models of interactions between phytoplankton, viruses and grazers as a means to quantitatively constrain the flow of carbon through marine microbial ecosystems. We augment population models with a synthesis of laboratory‐based estimates of prey, predator and viral life history traits that constrain transfer efficiencies. We then apply the model framework to estimate loss rates in the California Current Ecosystem (CCE). With our empirically parameterized model, we estimate that, of the total losses mediated by viruses and microzooplankton grazing at the focal CCE site, 22 ± 3%, 46 ± 27%, 3 ± 2% and 29 ± 20% were directed to grazers, sloppy feeding (as well as excretion and respiration), viruses and viral lysate respectively. We identify opportunities to leverage ecosystem models and conventional mortality assays to further constrain the quantitative rates of critical ecosystem processes.

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

Contrasting Controls on Microzooplankton Grazing and Viral Infection of Microbial Prey - David Talmy; Stephen J. Beckett; Adam B. Zhang; Darcy A. A. Taniguchi; Joshua S. Weitz; Michael J. Follows (Frontiers in Marine Science, 2019)

Quantifying Tradeoffs for Marine Viruses - Nicholas R. Record; David Talmy; Selina Våge (Frontiers in Marine Science, 2016)

An optimality model of photoadaptation in contrasting aquatic light regimes - David Talmy; Jerry Blackford; Nick J. Hardman-Mountford; Alex J. Dumbrell; Richard J. Geider (Limnology and Oceanography, 2013)
To investigate photoacclimation of phytoplankton adapted to different aquatic light regimes, a physiologically explicit phytoplankton optimality model was applied in two contrasting environments: constant irradiance vs. dynamic irradiance associated with oceanic mixed layers. Nitrogen was assumed to be partitioned between cellular components associated with light harvesting, carbon fixation, biosynthesis, and photoprotection. The model was used to predict how resources are (re)distributed to optimize growth in the different environments. Optimal intracellular nitrogen allocation in dynamic environments was associated with constitutive investment in Calvin cycle enzymes; in contrast, in the static environment Calvin cycle allocation was reduced at low light. Furthermore, reduced allocation to components associated with photoprotection in static environments led to heavily inhibited photosynthesis‐irradiance response consistent with that of Prochlorococcus adapted to relatively stable oligotrophic gyres. In contrast, photosynthetic response in the diatom Skeletonema costatum was better explained by maintenance of photoprotection components across a range of integrated light doses. Limited range of chlorophyll : C in Thalassiosira pseudonana was consistent with optimization of resource allocation to light‐harvesting components in dynamic environments, in contrast to the relatively wide range in allocation to light harvesting predicted by the model in static environments and chlorophyll cell −1 observed in high‐light‐adapted Prochlorococcus . The model was used to explain variability of the photosynthesis‐irradiance response of samples from the Celtic and Irish Seas. Photoacclimation state is a consequence of optimization of resource allocation to the set of environmental parameters (e.g., surface irradiance, depth of mixing, and light attenuation) that influence light variability.